Genetic diversity of two local Yunnan chicken breeds and their relationships with red jungle fowl - LU Junxian; JIA Xiaoxu; TANG Xiujun; FAN Yanfeng; TANG Mengjun; GAO Yushi; SU Yijun (浙江大学学报. 农业与生命科学版, 2016)
Chickens are an important animal genetic resource and the conservation of local breeds is an issue for preservation. With these highly diversified geographical environments, coupled with copious precipitation, adequate sunlight, and long frost-free periods, Yunnan Province has high biodiversity, including habitats for several ancestral species of domestic chicken and which has been suggested to be a center of domestication of chicken.Daweishan mini and Chahua are typical local chicken breeds in Yunnan Province. This study evaluated the genetic diversity and origins of the two breeds by analyzing their mtDNA sequence polymorphisms. Blood samples were collected from 30 of each breed. Their complete D-loop sequences were PCR amplified, sequenced and compared with the DNA data of five red jungle fowl (Gallus gallus) subspecies annotated in the GenBank.The results indicated that D-loop regions of the two local Yunnan chicken breeds were 1 231-1 232 bp, with a base C deficiency from 859 bp site in the 1 231 bp haplotype. Nineteen polymorphic sites were identified across the complete mtDNA D-loop region sequence. The eight haplotypes observed in the two local chicken breeds belonged to four previously published clades, i.e. Clades A, B, D and E. Of these clades, A and B were dominant. Clades A and B both contained three haplotypes, whereas Clades D and E both contained one haplotype. Clades A and B were clustered with G. g. spadiceus indicating that the two clades may originated from this subspecies. Clade E was clustered with G. g. murgh indicating that this clade may originated from this continental subspecies. The other haplotypes were contained in Clade D, which originated from multiple maternal origins. There were diversities in the middle of the mtDNA D-loop sequences of the two local breeds, which may result from multiple maternal origins. These data indicate that G. g. spadiceus contributed more to the evolution of the two local Yunnan breeds than the other four subspecies tested. The haplotypic diversity within the Daweishan mini chicken (0.685) and Chahua (0.476) was lower than those of breeds studied using the hypervariable I (HVI) segment of the D-loop in other chickens of Yunnan Province.Determining the genetic background of domestic chicken breeds local to Yunnan Province and their relationships with red Jungle fowl could improve the understanding of chicken domestication. In contrast to other chickens of Yunnan Province, the two chicken breeds studied here had lower diversity at mitochondrial levels. Due to their possible contribution to past and recent domestication, the two breeds deserve a conservation attention.